The Synaptic Scaling Literature: A Systematic Review of Methodologies and Quality of Reporting - Moulin, Thiago C.; Rayêe, Danielle; Williams, Michael J.; Schiöth, Helgi B. (Frontiers in Cellular Neuroscience, 2020)
The maintenance of the excitability of neurons and circuits is a fundamental process for healthy brain functions. One of the main homeostatic mechanisms responsible for such regulation is synaptic scaling. While this type of plasticity is well-characterized through a robust body of literature, there are no systematic evaluations of the methodological and reporting features from these studies. Our review yielded 168 articles directly investigating synaptic scaling mechanisms, which display relatively high impact, with a median impact factor of 7.76 for the publishing journals. Our methodological analysis identified that 86% of the articles made use of inhibitory interventions to induce synaptic scaling, while only 41% of those studies contain excitatory manipulations. To verify the effects of synaptic scaling, the most assessed outcome was miniature excitatory postsynaptic current (mEPSC) recordings, performed in 71% of the articles. We could also observe that the field is mostly focused on mechanistic studies of the synaptic scaling pathways (70%), rather than the interaction with other types of plasticity, such as Hebbian processes (4%). We found that more than half of the articles failed to describe simple features, such as regulatory compliance statements, ethics committee approval, or statements of conflict of interests. In light of these results, we discuss the strengths and pitfalls existing in synaptic scaling literature.